Job satisfaction and nurse performance: a cross-sectional study in a hospital surgical ward - Dirdjo, Maridi Marsan; R. Syahab, Subhan; Sureskiarti, Enok; Suwanto, Suwanto (Jurnal Ilmu Kesehatan, 2023)
Abstract: Employee performance has always been a major challenge in the management of organizations such as hospitals. Measuring the performance of hospital employees, especially nurses, is a very interesting topic considering that nurses are the largest workforce, which is around 50-60% of all health workers in the hospital. Research on job satisfaction in nurses related to performance is still important to do, to encourage overall hospital performance. Purpose: aim this research is to examine the relationship between job satisfaction and nurse performance. Method: This study used a correlational descriptive study with a cross-sectional design. The population of this research is practicing nurses with total sampling technique. Data was collected using the Index Work Satisfaction (IWS) questionnaire and the Six Dimensional Scale of Nursing Performance. Statistical analysis using the Chi Square test. Results: 60.6% of nurses are satisfied with their work, while 53.5% of nurses still have poor performance. This study has revealed a significant relationship between job satisfaction and the performance of nurses in the surgical treatment room (p-value 0.002; α: 0.005) with OR showing 6.188 meaning that nurses who are dissatisfied with their work have the opportunity to perform less well 6.2 times, when compared with nurses who are satisfied in their jobs. These results can be used by hospital nursing managers that in order to improve nurse performance they must consider the job satisfaction of their nurses.